A26 A SYSTEMTIC REVIEW OF MONOGENIC INFLAMMATORY BOWEL DISEASE: CLINICAL PHENOTYPE AND GENOTYPE. (4th March 2021) - Nambu, R; Warner, N; Mulder, D J; Muise, A
Abstract: Background: Advances in genomic technologies have led to an increase in reports of monogenic inflammatory bowel disease (IBD). The majority of the studies on monogenic IBD have focused only on young children aged <6 years. There are no detailed reports containing a comprehensive picture of monogenic IBD with specific numbers on the clinical features, genetic profiles and disease course. Since each gene-specific cause of monogenic IBD is rare, it is difficult to collect cases in a single study even with international cohort studies. Aims: To elucidate a comprehensive picture of monogenic IBD, we conducted a systematic review of all reported cases of monogenic IBD. Methods: A systematic review of MEDLINE articles published between January 2000 and December 2019 was conducted. 662 monogenic IBD cases were identified from 273 eligible articles. Data on clinical manifestation, genotype, and management were collected. Results: The most frequently reported genes causative of monogenic IBD patients were IL10RA, CYBB, IL10RB, and TTC7A (Figure). In total, 64.8% of patients developed IBD before six years old, 15.6% between ages 10 and 17.9 years, and 11.6% at age 18 years or older. Only 32.7% had any history of extra-intestinal manifestation (EIM) before IBD onset. There was substantial difference in the onset age groups and the underlying monogenic disorders. 74.4% developed at least one EIM during their clinical course. The most common EIMs were atypical infection (44.1%), dermatologic abnormality (39.2%), autoimmunity (22.7%) and lymphoid organ abnormality (11.5%). Autosomal recessive (62.8%) was the most common inheritance pattern, and missense-variants (44.3%) were the most identified type of genetic variants. Deletions including CNVs, intronic, synonymous and inversion, which have the possibility to be overlooked by whole exome sequencing were shown in some cases. Bowel surgery, biologics, and hematopoietic stem cell transplantation were performed in 28.3%, 32.8%, and 24.4% of patients, respectively. Conclusions: Monogenic IBD diagnosis and management is a challenging clinical problem across age groups; the EIMs are more diverse and the management is evidently more difficult compared to non-monogenic IBD. An improved understanding of the characteristics of the genes and underlying disease processes in monogenic IBD is necessary for effective management. Funding Agencies: CAG, CIHRUehara Memorial Foundation Fellowship